Seven into two: Principal components analysis and the Olympic heptathlon - Fanshawe, T. (Significance, 2012)
Of all the contests at the Olympic Games, it is surely the multi-event disciplines that provide the most challenging all-round tests of athletic supremacy. But how can we measure who is the most deserving winner when competitors are performing in not just one event, but five, or seven, or ten? Multi-event competitions at the Olympic Games date to at least the eighth century BC, when the pentathlon was introduced. Mythically the creation of the Greek hero Jason, the original competition consisted of five events: running, standing long jump, discus, javelin and wrestling. The modern pentathlon, the brainchild of the founder of the Olympic movement, Pierre de Coubertin, stands alongside the men`s decathlon and the women`s heptathlon as a prominent multi-event discipline in the Games today. Table 1 shows the contributing events for each. An obvious question arises. In, say, the decathlon, suppose one athlete wins the first five events, and another the second five events; which is the better athlete? Which should be declared the winner? And does the balance of events used favour athletes with particular strengths? One could subdivide the ten events into four that involve jumping in some form - long jump, high jump, pole vault and hurdles - and six that do not. Or one could use the more familiar classification of four track events and six field events. Decisions about the "best" decathlete, heptathlete or pentathlete contain complexities.